Liposome-based nanoparticles impact on regulatory and effector phenotypes of macrophages and T cells in multiple Sclerosis patients. (January 2023) - Tredicine, Maria; Ria, Francesco; Poerio, Noemi; Lucchini, Matteo; Bianco, Assunta; De Santis, Federica; Valentini, Mariagrazia; De Arcangelis, Valeria; Rende, Mario; Stabile, Anna Maria; Pistilli, Alessandra; Camponeschi, Chiara; et al.
Abstract: Current available treatments of Multiple Sclerosis (MS) reduce neuroinflammation acting on different targets on the immune system, but potentially lead to severe side effects and have a limited efficacy in slowing the progression of the disease. Here, we evaluated in vitro the immunomodulatory potential of a new class of nanoparticles – liposomes, constituted by a double-layer of phosphatidylserine (PSCho/PS), and double-faced, with an outer layer of phosphatidylserine and an inner layer of phosphatidic acid (PSCho/PA), either alone or in the presence of the myelin basic protein (MBP) peptide (residues 85–99) (PSCho/PS-MBP and PSCho/PA-MBP). Results showed that PSCho/PS are equally and efficiently internalized by pro- and anti-inflammatory macrophages (M1 and M2 respectively), while PSCho/PA were internalized better by M2 than M1. PSCho/PS liposomes were able to inhibit the secretion of innate pro-inflammatory cytokine IL-1β. PSCho/PS liposomes expanded Tregs, reducing Th1 and Th17 cells, while PSCho/PA liposomes were unable to dampen pro-inflammatory T cells and to promote immune-regulatory phenotype (Treg). The ability of PSCho/PS liposomes to up-regulate Treg cells was more pronounced in MS patients with high basal expression of M2 markers. PSCho/PS liposomes were more effective in decreasing Th1 (but not Th17) cells in MS patients with a disease duration >3 months. On the other hand, down-modulation of Th17 cells was evident in MS patients with active, Gadolinium enhancing lesions at MRI and in MS patients with a high basal expression of M1-associated markers in the monocytes. The same findings were observed for the modulation of MBP-driven Th1/Th17/Treg responses. These observations suggest that early MS associate to a hard-wired pro-Th1 phenotype of M1 that is lost later during disease course. On the other hand, acute inflammatory events reflect a temporary decrease of M2 phenotype that however is amenable to restauration upon treatment with PSCho/PS liposomes. Thus, together these data indicate that monocytes/macrophages may play an important regulatory function during MS course and suggest a role for PSCho/PS and PSCho/PS-MBP as new therapeutic tools to dampen the pro-inflammatory immune responses and to promote its regulatory branch.